Ludic Surveillance and Semogenesis of Choice in The Uber Game - Fawzy, Rania Magdi (Public Journal of Semiotics, 2026)
News gamification integrates video game mechanics such as points, badges, and challenges, transforming the experience of news reading into an interactive, competitive process. This commodifies users’ news consumption, aligning it with the logic of neoliberal self-entrepreneurship and engagement metrics. To this end, this study examines how the gamified news feature story The Uber Game transforms choice into a semiotic mechanism of control, where ludic surveillance, regulates players’ decision-making through algorithmic incentives and constraints. Drawing on Halliday’s concept of semogenesis, this study argues that The Uber Game encodes choice as a structured process, where players navigate a predetermined system of algorithmic incentives and semiotic constraints. The Uber Game, developed by The Financial Times, offers players a first-hand experience of life as a full-time Uber driver, immersing them in the precarious conditions of the gig economy. The study unravels how the game simulates platformized conditioning and labour discipline within Uber’s broader system. The semiosis of choices the players enact is not isolated within the game context, but rather is part of a socially conditioned discourse that is related to gig work and corporate algorithms. By mapping these dimensions, this study not only analyses meaning-making within the gamified system but also reflects on the broader gig economy structure that Uber exemplifies.